Engineered Rhodobacter capsulatus as a Phototrophic Platform Organism for the Synthesis of Plant Sesquiterpenoids - Troost, Katrin; Loeschcke, Anita; Hilgers, Fabienne; Özgür, Armagan Yakup; Weber, Tim Moritz; Santiago-Schübel, Beatrix; Svensson, Vera; Hage-Hülsmann, Jennifer; Habash, Samer S.; Grundler, Florian M. W.; Schleker, A. Sylvia S.; Jaeger, Karl-Erich; et al. (Frontiers in Microbiology, 2019)
Sesquiterpenoids are a large class of natural compounds offering manifold properties valuable for food, cosmetics, agriculture and pharma industry. Production in microorganisms is a sustainable approach to provide sesquiterpenoids for research and industrial use independent of their natural sources. This requires the functional transfer of the respective biocatalytic pathways in an adequate host microorganism offering a sufficient supply of precursors that is ideally adjusted to the individual demand of the recombinant biosynthesis route. The phototrophic purple bacterium Rhodobacter capsulatus offers unique physiological properties that are favorable for biosynthesis of hydrophobic terpenes. Under phototrophic conditions, it develops a large intracytoplasmic membrane suitable for hosting membrane-bound enzymes and metabolites of respective biosynthetic pathways. In addition, Rhodobacter harbors an intrinsic carotenoid biosynthesis that can be engineered towards the production of foreign terpenes. Here, we evaluate R. capsulatus as host for the production of plant sesquiterpenoids under phototrophic conditions using patchoulol and valencene as a proof of concept. The heterologous expression of patchoulol synthase PcPS from Pogostemon cablin as well as the valencene synthases CsVS from Citrus sinensis and CnVS from Callitropsis nootkatensis led to the production of the respective sesquiterpenoids in R. capsulatus. To analyze, if gradually adjustable formation of the key precursor farnesylpyrophosphate (FPP) is beneficial for sesquiterpene synthesis under phototrophic conditions, the intrinsic 1-deoxy-D-xylulose 5-phosphate (DXP) pathway genes as well as the heterologous mevalonate pathway genes were modularly expressed in various combinations. To this end, different plasmids and chromosomally integrated expression tools were developed harboring the strong and tightly controlled Pnif promoter for heterologous gene expression. Notably, comparative studies identified a distinct combination of precursor biosynthetic genes as best-performing setup for each of the tested sesquiterpene synthases. In summary, we could demonstrate that R. capsulatus is a promising alternative platform organism that is suited for sustainable sesquiterpenoid formation under phototrophic cultivation conditions. A modular engineering of R. capsulatus strains via tailored co-expression of FPP biosynthetic genes further allowed adaptation of sesquiterpene precursor formation to its catalytic conversion by different plant terpene synthases.